2020
DOI: 10.3389/fmicb.2020.574146
|View full text |Cite
|
Sign up to set email alerts
|

Successional Change of the Fungal Microbiome Pine Seedling Roots Inoculated With Tricholoma matsutake

Abstract: The pine mushroom (Tricholoma matsutake; Agaricales, Tricholomataceae) is an ectomycorrhizal fungus that produces a commercially valuable, edible mushrooms. Attempts to artificially cultivate T. matsutake has so far been unsuccessful. One method used to induce T. matsutake to produce fruiting bodies of in the wild is shiro (mycelial aggregations of T. matsutake) transplantation. In vitro ectomycorrhization of T. matsutake with seedlings of Pinus densiflora has been successful, but field trials showed limited p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…Park and his colleagues conducted in vitro transplantation of P. densiflora seedlings inoculated with T. matsutake and showed the different results from our study covering several points [ 54 ]. Our study did not have a significant change of the transplantation which they conducted, but only observed seasonal changes and regional differences in the wild environment in which T. matsutake grows, so there was a clear difference from the in vitro experiment.…”
Section: Resultsmentioning
confidence: 87%
“…Park and his colleagues conducted in vitro transplantation of P. densiflora seedlings inoculated with T. matsutake and showed the different results from our study covering several points [ 54 ]. Our study did not have a significant change of the transplantation which they conducted, but only observed seasonal changes and regional differences in the wild environment in which T. matsutake grows, so there was a clear difference from the in vitro experiment.…”
Section: Resultsmentioning
confidence: 87%
“…Other studies have already reported a negative impact on Trichoderma spp. inoculations on plant microbiome diversities (Park et al 2020;Stummer et al 2022;Sui et al 2022). According to the LEfSe analysis, fungal pathogens responsible to grapevine trunk diseases, like Ilyonectria, and Diaporthe (Gramaje et al 2018) reduced overtime, and/or in plants inoculated with Ta SC1.…”
Section: Discussionmentioning
confidence: 99%
“…The production of Tricholoma matsutake , a symbiotic pine mushroom, has declined due to climate change and newly occurring pine tree diseases ( 1 , 2 ), emphasizing the need to understand the mycorrhizal symbiosis with coniferous trees ( 3 , 4 ). Although genomes of T. matsutake have been sequenced ( 5 7 ) ( Table 1 ), they are highly fragmented, limiting in-depth molecular analysis.…”
Section: Announcementmentioning
confidence: 99%